STUDY OF ANGIOTENSIN-I CONVERTING ENZYME INHIBITORY PEPTIDES DERIVED FROM Ficus pumila var. awkeotsang SEEDS HYDROLYSATE - Ningrum, Sugiyati; Jue Liang Hsu (Fakultas Teknologi Pertanian Universitas Brawijaya, 2024)
Hypertension also known as high blood pressure that has associated with multi-metabolic pathways such as the renin-angiotensin-aldosterone system (RAAS). There have been several synthetic ACE inhibitory drugs used clinically as therapeutics for hypertension. However, synthetic drugs showed side effects on human health after long-term use. Therefore, alternative natural ACE inhibitors from food-derived are necessary to develop. The study aimed to examine the activity of angiotensin-I converting enzyme inhibitory peptides derived from Ficus pumila var. awkeotsang seeds hydrolysate and to study the efficiency of enzymatic digestion. This study used four enzymes (trypsin, pepsin, thermolysin, and chymotrypsin) to release bioactive peptides from Ficus pumila var. awkeotsang seeds that could exhibit an antihypertensive effect. The results showed that Ficus pumila var. awkeotsang trypsin hydrolysate has the highest ACEI activity, 90.37%, and the IC50 reached 169±3.5 µg/mL. Then, the hydrolysate produced by trypsin has the highest degree of hydrolysis, 4%, after 8 hours of incubation. Hence, Ficus pumila var. awkeotsang seeds hydrolysate could develop as an alternative natural product that is responsible for ACE-inhibitory activity.